Optimalisasi Sertifikasi Dan Karir Guru - Yahya, Vilzati, Sisca Mediyanti, Masbur, Ainul Ridha , Yahya (JKA, 2024)
This study deals with the optimization of teacher certification and career as an attempt to improve the quality of education in the face of the changing challenges of the times. This optimization process not only covers formal aspects of certification, but also teacher career development that involves innovation, leadership, and adaptability. The benefits of teacher certification and career optimization include improved teaching quality, improved teacher professionalism, and improved global competitiveness. Teachers who have good certifications and continue to grow in their careers tend to provide teaching that is more tailored to students’ needs. Moreover, certification & career development also rewards teacher work and encourages positive innovation. The study uses the International Commitment to the Community (ICC) as a case study. In these activities, the Academic Sharing Action Community (KABA) has prepared itself well, established cooperation with various parties, and established strategic measures. The results of the implementation of the International CPC show the positive impact and success of the event depends on mature preparation as well as active participation of various parties.